2017
DOI: 10.1016/j.bbamcr.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

AMPK downregulates ALK2 via increasing the interaction between Smurf1 and Smad6, leading to inhibition of osteogenic differentiation

Abstract: Activin A receptor type I or activin receptor-like kinase 2 (ACVRI/ALK2) belongs to type I TGF-β family and plays an important role in bone development. Activating mutations of ALK2 containing the R206 to H mutation, are present in 95% in the rare autosomal genetic disease fibrodysplasiaossificansprogressiva (FOP), which leads to the development of ectopic bone formation in muscle. The effect of AMP-activated protein kinase (AMPK) activation on ALK2R206H-mediated signaling in fibroblast obtained from a FOP pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 39 publications
5
34
1
Order By: Relevance
“…Since the purpose of the present study was to elucidate how thioridazine and fluphenazine induced differentiation of CSC‐like cells instead of observing cell death or anti‐angiogenesis, we included AMPK and c‐Met in the list of candidate cellular target molecules regulated by thioridazine and fluphenazine together with Akt and mTOR (Figure ). This because AMPK and c‐Met could stimulate cell differentiation when they are activated or inhibited . Among these four cellular molecules, AMPK appeared to be the target molecule for inducing differentiation of C5A cells since its phosphorylation was inhibited dose‐dependently by thioridazine and fluphenazine, but not by promazine.…”
Section: Discussionmentioning
confidence: 99%
“…Since the purpose of the present study was to elucidate how thioridazine and fluphenazine induced differentiation of CSC‐like cells instead of observing cell death or anti‐angiogenesis, we included AMPK and c‐Met in the list of candidate cellular target molecules regulated by thioridazine and fluphenazine together with Akt and mTOR (Figure ). This because AMPK and c‐Met could stimulate cell differentiation when they are activated or inhibited . Among these four cellular molecules, AMPK appeared to be the target molecule for inducing differentiation of C5A cells since its phosphorylation was inhibited dose‐dependently by thioridazine and fluphenazine, but not by promazine.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, the serum levels of TGF-β1 in patients with type 2 diabetes receiving metformin are lower than those taking other glucose lowering medicine. Interestingly, the inhibitory effect of AMPK on TGF-β signaling is not just limited to Alk5/Smad2/3 paradigm, but also extends to BMP/ALK1/2/Smad1/5 signaling [82,133]. We have recently found that metformin inhibits ALK1-mediated tube formation and angiogenesis in matrigel plug assay [133].…”
Section: The Mechanisms Underlying the Opposite Effects Of Ampk Onmentioning
confidence: 99%
“…AMPK inhibitor compound C abolished the metformin-induced osteogenic differentiation of SHEDs. Our data and abundant literature evidence indicate osteogenic effects of metformin, but Jeyabalan and colleagues reported no effects of metformin on osteogenesis in vivo[40,41]. It is likely that the seed cells used in some studies did not have sufficient osteogenic potential or that the animal models were not close enough to the clinical situation of bone regeneration.…”
mentioning
confidence: 53%